2003
DOI: 10.1080/09540120310001618702
|View full text |Cite
|
Sign up to set email alerts
|

Women's acceptability and husband's support of rapid HIV testing of pregnant women in India

Abstract: This study examined acceptability among pregnant women and their husbands for HIV testing within the antenatal clinic (ANC) and delivery room (DR) of a government hospital in Pune, India from September 2000 to November 2001. Acceptance of HIV counselling and testing was high with 83% of eligible women in the antenatal clinic (851 of 1025) and 68% of eligible women in the delivery room (417 of 613) getting tested on the same day. Structured interviews were conducted on 94 pregnant women in the ANC 50 women in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 6 publications
6
29
0
Order By: Relevance
“…When women tested for HIV outside of the antenatal setting, however, without first consulting their husbands, men became suspicious of their motives. These findings are consistent with another study in India that found that men are generally supportive of their wives testing as part of antenatal care (Shankar, Pisal, Patil, Joshi, & Suryavenshi, 2003). Taken together, findings from these studies provide evidence that supports the adoption of a routine provider-initiated HIV testing approach within the antenatal setting for several reasons.…”
Section: Discussionsupporting
confidence: 90%
“…When women tested for HIV outside of the antenatal setting, however, without first consulting their husbands, men became suspicious of their motives. These findings are consistent with another study in India that found that men are generally supportive of their wives testing as part of antenatal care (Shankar, Pisal, Patil, Joshi, & Suryavenshi, 2003). Taken together, findings from these studies provide evidence that supports the adoption of a routine provider-initiated HIV testing approach within the antenatal setting for several reasons.…”
Section: Discussionsupporting
confidence: 90%
“…When tested in the private sector, women were less likely to obtain any form of pre-test or post-test information, including informed consent. This is congruent with previous studies that raise concerns regarding the quality of testing in the private sector (Kielmann et al, 2005;Sheikh et al, 2005). Inadequate procedures around testing among women in the private sector have been linked to PPs' perceptions of their female patients being too emotionally volatile or too uneducated to be able to understand and cope with a positive test result (Datye et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…However, while providers' sharing of test results with individuals other than the patient is an ethical concern, it may well represent a meaningful, if not inevitable, local adaptation in a cultural context where family ties take precedence over individual autonomy. As suggested by researchers working in India (Kielmanna et al, 2005;Sarvade et al, 2000;Shankar et al, 2003) as well as elsewhere (Cassell, 2005;Molyneux, Wassenaar, Peshu, & Marsh, 2005;Pace, Grady, & Emanuel, 2003), concepts of informed consent and counselling are often interpreted and implemented differently in different settings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This interdependence of education, knowledge, and acceptance of the test is consistent with the results of studies conducted in other countries, and is unaffected by geographical, cultural, or ethnic differences [11][12][13].…”
Section: Discussionsupporting
confidence: 83%